Optimalisasi Metode KWL dalam Meningkatkan Pemahaman Teks Bahasa Arab pada Keterampilan Qiro’ah Siswa Kelas XI - Berliana; Muflihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low reading skill is caused by a monotonous learning process, resulting in very little student interest in learning Arabic. Therefore, to improve students’ comprehension of Arabic texts and their interest in learning, the researcher offers a solution by applying the Know–Want to Know–Learned (KWL) learning method in teaching Arabic to grade XI-I students at Madrasah Aliyah. This study employs a quasi-experimental design with a One Group Pretest–Posttest Design, using Classroom Action Research (CAR) techniques conducted in two phases. The sample of this study consisted of 34 students from grade XI-I of Madrasah Aliyah. Before the implementation, students’ reading comprehension ability in Arabic texts achieved an average mastery score of 29.41%. The results after implementing the KWL method in phase I showed an improvement to 44.11%, an increase of 14.70% from the initial score. In phase II, the score rose significantly to 91.17%, indicating that students had successfully mastered Arabic text comprehension through the KWL method. The results of applying the KWL method in Arabic language learning proved effective in improving students’ understanding of Arabic reading texts (maharah qira’ah) among grade XI-I students.